Social Value Orientation Moderated the Effect of Acute Stress on Individuals’ Prosocial Behaviors - Ying, Liuhua; Yan, Qin; Shen, Xin; Zhang, Chengmian (Frontiers in Psychology, 2022)
Acute stress is believed to lead to prosocial behaviors via a “tend-and-befriend” pattern of stress response. However, the results of the effect of acute stress on prosocial behavior are inconsistent. The current study explores the moderating effect of social value orientation on the relationship between acute stress and individuals’ prosocial behaviors. Specifically, eighty-one participants were selected and underwent the Trier Social Stress Test (or were in the control group), followed by the third-party punishment task and the dictator game. The results showed that, in general, the main effect of condition or Respiratory Sinus Arrhythmia (RSA) reactivity on individual prosocial behaviors were significant and did not vary between genders. Furthermore, social value orientation (i.e., prosocial or self-orientation) might moderate the impact of RSA reactivity on the amount of punishment in the third-party punishment task. That is, individuals with self-orientation exhibited more punishment as RSA reactivity decreased, while the effect did not occur for individuals with prosocial orientation. Taken together, the findings of the current study provide further evidence for the “tend-and-befriend” hypothesis and highlight the underlying physical mechanisms as well as the individual dependence of the effect of psychosocial stress on social behavior.